(5RS)‐5‐(4‐Methoxyphenyl)‐2‐(methylsulfanyl)benzo[g]pyrimido[4, 5‐b]quinoline‐4, 6, 11(3H, 5H, 12H)‐trione, with Z′ = 3, forms a three‐dimensional hydrogen‐bonded framework containing five types of hydrogen bond. Issue 1 (15th January 2014) - Castillo, Yelder A.; Zapata, Luis F.; Trilleras, Jorge; Cobo, Justo; Glidewell, Christopher
<x xml:space="preserve">Abstract</x> The title compound, C23H17N3O4S, crystallizes with Z′ = 3 in the space group P<inline-graphic xlink:href="ark:/27927/pgh6n17r6v" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />. Two of the three independent molecules are broadly similar in terms of both their molecular conformations and their participation in hydrogen bonds, but the third molecule differs from the other two in both of these respects. The molecules are linked by a combination of N—H...O, N—H...N, C—H...O, C—H...N and C—H...π(arene) hydrogen bonds to form a continuous three‐dimensional framework structure within which a centrosymmetric six‐molecule aggregate can be identified as a key structural element.